ChemInform Abstract: The ADOR Mechanism for the Synthesis of New Zeolites. Issue 48 (December 2015) - Eliasova, Pavla; Opanasenko, Maksym; Wheatley, Paul S.; Shamzhy, Mariya; Mazur, Michal; Nachtigall, Petr; Roth, Wieslaw J.; Morris, Russell E.; Cejka, Jiri
Abstract: Review: ADOR: Assembly‐Disassembly‐Organization‐Reassembly; 206 refs.